GEMAS: Indium in agricultural and grazing land soil of Europe — Its source and geochemical distribution patterns - Ladenberger, Anna; Demetriades, Alecos; Reimann, Clemens; Birke, Manfred; Sadeghi, Martiya; Uhlbäck, Jo; Andersson, Madelen; Jonsson, Erik (Journal of geochemical exploration, 2015)
Indium is a very rare element, which is usually not reported in geochemical data sets. It is classified as a critical metal, with important applications in the electronics industry, especially in the production of solar panels and liquid-crystal displays (LCDs). Over 4000 samples of agricultural and grazing land soil have been collected for the “Geochemical Mapping of Agricultural and Grazing Land Soil of Europe” (GEMAS) project, carried out by the EuroGeoSurveys Geochemistry Expert Group. Indium concentrations in soil have been analysed using aqua regia extraction followed by ICP-MS. Median values of In for both land use types are nearly identical, 0.0176mg/kg for agricultural soil and 0.0177mg/kg for grazing land soil. The spatial distribution patterns of In in European soil are mainly controlled by geology and the presence of Zn and Sn mineralisation. The preference of In to accumulate in the fine-grained fraction of soil with high clay content dominates the major anomaly patterns on the geochemical maps. In the Mediterranean region, secondary In enrichment is visible in karst areas. A notable feature of the In spatial distribution is the large difference between northern and southern Europe, with median values of 0.012 and 0.021mgIn/kg, respectively, suggesting that, in addition to lithology, weathering and climate are important factors influencing In soil enrichment over time. •Continental-scale geochemical mapping provides indium content in agricultural soil.•The distribution pattern is strongly controlled by natural sources.•Anthropogenic contamination cannot be detected at the continental scale.•Any possible contamination signal overlaps spatially with natural sources of metals.